Location via proxy:   [ UP ]  
[Report a bug]   [Manage cookies]                

2008 (full) 2

Download as pdf or txt
Download as pdf or txt
You are on page 1of 46

sin(3x) +

O
lim (2x3 + 6) =
- = 2
x +0x(2x2 + 3)
6 4 2k + 1
4 -
+ =

7 = 24 + 1

O 2k
u
=

=
6

3 (cos (4x1)2(- 4 sin (4x1(


(4x1(
O - 12 (los (4x1)* (sin
g
f(x) = 6x2-6x -

12

2)
+ '(x) = 0 = 6(x2 -
x - = 0

X -
I 2
6(x -

2)(x + 1) = 0

t 2 x -1
↓ O x =

fl O =
-

f >
- mar- min

Y
x1 = 1

m(x xi) 41 =
(211) 15 (151)
-

y y1
-
= -

|t(2) = 2
2 2)(x 1)
O
y
=
-
-

(2x 1)5(1)
10(2x 1) "(x + 1) +
-

2(X 2) m =
y 2
-
-
- =

y = 21x - 19
= 10(2(1) 1) "(1 + 1)
- + (2(1) 1)5(1)
-

20 + 1 = 21
u = v

du = x

O dx = 25 de

a du

2
Je "du
2e" + 1

2eF + C

O
[0 2] , ,
[2 4], , [415]

+)
=
2) -
+f -
(2)
-

8 + 8 + 12 = 52
y + k + u +

2n + 32 = 52

2u = 26

u = 10
O
x(2) x(1)
-
=

SY -
672dE

x(2) -
x(1) = 4t
-
at 3)
x(2) -
x(1) =
(0 -
16) -
(4 2) -

x(1) ( 2) (2)
X(2)
-
-
-
=

x(2) = -
10 + 7 =
-
3

y
=
3H A -

2 V A >
- x2 + b = 0
x
.

- x2 =
-
b
f(x) 3
- lim Fb
=
* =

- = +&
3 2 = ~b -

b
4
g
X = -

a = 3
b =
-

4
x X +
V
-

=
4 = e
X
v1 1
-

=
y = -
e

x(x 1) (e x)
-
-

e +
-

O (x + 1)2

-(2) e
=
-e
-

O
f(e) -
f(r) =

Sedx
fle)-f(re) =

zinkle
f(e) - f(re) = 2 (1 -

z)
1
f(e) - 5 =

f(e) = 6
(x + 2+
3
+ 1dx

E + +

G
(2 '(x
%
e
= 2
=
eYx = 2
=

O
X y

O
f(x)@
+ T
X 2x2 = -
5x

O
-

6x -
2x2 = 0

2x(3 -
x) = 0

3 x = 0 X = 3

9
,

x
-
2x2 + 5xdx
,

1836x - 2x2dx

3x2 -

2x3/3 =
(27 1) - -
0 = 9

x1 = 1

G
= 4
y1
m = 3

y
-

y1 = m(x -

xi)

3(x -
1)
4
y
-
=

Y = 3x + 1

3(1 2) + 1 3 6
.
+ 1 =
4 6
.

f (1 2)
=
.

. =
O f(x) = 3x2 -
12x

6x 12
f((x)
-

6(x 2) - =
0
f"(x) = 0 =
x = 2

X 2

f" -
O +

f
M j

O
p(z) g(l)
9,3p'(x(dx
-

(p -

p +
4) - (1 -
3 + 4)
11 -
2 = 2
A D

f(x) = 0
10
8 b u =
x 0 x = a x = ,
=
, ,

So" H(x)de O O b 10
f (a) -
f(0) =
x

22 max fl ot o - 6 t 6
f(a) = 20 + 2
=

f 1101 -
f(x) =
9:
'Al de f
x- y & T
-
20
f (10) = 18 + z =

~ f (x) = 0

X (x -
2)(x
-

3)(X -

y) = 0

X x = 2
,
x = 3
, x = 4

O
y 2 3 4

fl ↓ 8 -
E - g t

Saddle
max
f - Y min X

312(x
-
413
2)(X
-

(x -

- =
+
-
+

(2 3)
,
t t
-
-
=

t =
-

t
-

(3 4) ,
= +
t

X >4
t
t
O PNE
rX = 2

c 2πV
πr2
=
A

O
=

= Cr = 2(

= 4
-
v =
E = 2

O
4 = x2v =
y (x +y 3x)) -
=
(y3 3)-

u' = 2x vi = y

2x
y + x2y' -
3 =
3yzy'

4 + y -
3 = 12y)

-
z = 11y
7
y
-
=

T
-
-

O
-

X
f'(x) = 0 f"(x) = 0

0
1- Inx
=

InX = 0
1
inx =

x = 1
X = C

X I X C

fl g t fl O
-

f M
f -

O
24x2 2x
f'(x)
-

16 4 = 20
+ /(2) 2
-

=
5

1- 25x2

G
O

153ax +
2) , +xax

15 + 2(6 + 4)
15 + 20 = 35
O

81 637
.

g(0)
=

O
g(o)-) ! Usin E
cit
g (6)
=

p(6) = 36 606
.
-
M

U O U

W
X
W

O
O
1 -

4( -

2cos2x)(e
-

sinz)
find roots
Graph &
# sign change
4 pts
=> inf .

pts .

by EUT O
ft + U

by MVT :

O F(() =
45342
f (2) =

14805-45 = 30 :

f'(22)
f (1) (f'(3)
<

O
&

G
184
=5)
" 0
1
S (*
.

=
+

.
-
~ zo =
O

7
-

3
-

O
& b 2 a

-
G
f -
7 A b ( d 7

O + 0 + 0 S t
f
-

f
YX + X + r 4XX

O "

↑ I B(t)dt =

:
u = 2 f(x) + 3 v = (+ g(x)
g
2f'(x)
vi =
p'(x)
41 =

(2 + '(x))(1 y() + + (2 + (1 3)(y'k))


+

( -

4)( -

2) + (9((4) = 44

g( + (3))
3

- q(8)
=
=

- (y( + (x))) = (x))

1
g'(f(x))
=

f(x) -

f'(3) .

g'(f(3)) = 1

p'(z) =

t
O
O

O
filx X = 1 .
464341888
= = 1
-
845270149

#1465) St
= -

=
D O 1 465 1 845 2
:
:

fl O t O
-

O t
so
neg
465)) F(2)
YXX
max

XX
↑ (1 :

f
max

You might also like